Analysis of Factors Affecting the Success of Sociocultural Education Approach in Preventing Tuberculosis in Tapanuli Selatan Regency - Edy Sujoko; Anto J. Hadi; Dewani Harahap; Matius Rantesalu; Edwinn Sallipadang; Farida Utaminingtyas; Juni Andriani Rangkuti; Asdi Lastari (Journal of Public Health and Pharmacy, 2025)
Introduction: Tuberculosis is still becoming one of the deathliest infectious diseases in the entire world and has become the most urgent public health challenge globally. This study aims to analyze the factors affecting the success of the sociocultural education approach in preventing Tuberculosis in Tapanuli Selatan Regency. Methods: Using a cross-sectional study approach, data were collected from the local community using purposive sampling. Data analysis was conducted to evaluate the influence of certain variables, including public education level, health service access, community participation in education programs, the use of social media in education campaigns, and health workers' support on the success of sociocultural education approach in preventing Tuberculosis through univariate, bivariate, and multivariate analyses. Results: The findings showed that community education level (p=0.001), health service access (p=0.001), community participation in education programs (p=0.001), social media use in education campaigns (p=0.001), health workers support (p=0.001) had a significant effect on the success of the sociocultural education approach in preventing Tuberculosis. Meanwhile, the variable of social media use in educational campaigns significantly influences public awareness and participation in efforts to prevent Tuberculosis, with an Exp value (B)=15.581 and a p=0.001 < ?=0.05 value. Conclusion: This research concludes that the tuberculosis prevention strategy in Tapanuli Selatan Regency needs to be supported with an integrated sociocultural education approach that accommodates the roles of social media, health service access, community participation, and health workers' support. This research suggests an increase in investment in health infrastructure, health workers' training, and a more intensive and guided education campaign to improve the community's awareness and participation in preventing Tuberculosis in the area.